2020
DOI: 10.1186/s12940-020-0571-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Food Quality Protection Act children’s health safety factor in the U.S. EPA pesticide risk assessments

Abstract: Background: The Food Quality Protection Act of 1996, or FQPA, required the Environmental Protection Agency to set allowable levels for pesticides in a way that would "ensure that there is a reasonable certainty that no harm will result to infants and children from aggregate exposure to the pesticide chemical residue." The act stipulated that an additional tenfold margin of safety for pesticide risk assessments shall be applied to account for pre-and postnatal toxicity and for any data gaps regarding pesticide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…A 2013 analysis by the United States Government Accountability Office (GAO) found that, out of 412 pesticide decisions, EPA retained the default 10x FQPA children’s safety factor only 22% of the time – it reduced the safety margin 75% of the time and increased it 3% [ 157 ]. A recent in-depth analysis of 47 non-organophosphate pesticides found that only 13% of acute food exposures and 12% of chronic food exposures incorporated any FQPA children’s safety factor whatsoever – and when it was included it was often in lieu of, not in combination with, a separate database uncertainty factor [ 158 ].…”
Section: How Disproportionate Pesticide Impacts Are Currently Perpetu...mentioning
confidence: 99%
See 1 more Smart Citation
“…A 2013 analysis by the United States Government Accountability Office (GAO) found that, out of 412 pesticide decisions, EPA retained the default 10x FQPA children’s safety factor only 22% of the time – it reduced the safety margin 75% of the time and increased it 3% [ 157 ]. A recent in-depth analysis of 47 non-organophosphate pesticides found that only 13% of acute food exposures and 12% of chronic food exposures incorporated any FQPA children’s safety factor whatsoever – and when it was included it was often in lieu of, not in combination with, a separate database uncertainty factor [ 158 ].…”
Section: How Disproportionate Pesticide Impacts Are Currently Perpetu...mentioning
confidence: 99%
“…EPA’s justification for rarely incorporating the protective safety factor comes from the language of the law itself, which gives the EPA discretion to reduce the 10x FQPA children’s safety factor if such a determination can be made “…on the basis of reliable data…” [ 159 ]. Yet EPA’s current practice is such that the only time it retains the FQPA children’s safety factor is in the rare case where there is overtly severe developmental toxicity in rodent studies, on the level of serious structural malformations or death [ 156 , 158 ]. When it decides to reduce or eliminate the FQPA children’s safety factor it is often based entirely on two or three rodent studies funded by the pesticide registrant, often conducted in the same laboratory [ 160 ].…”
Section: How Disproportionate Pesticide Impacts Are Currently Perpetu...mentioning
confidence: 99%
“…An additional factor, usually 3X or 10X (the Food Quality Protection Act safety factor), is incorporated into these risk assessments. Such an approach is underpinned by evidence that demonstrates that there are age-specific differences that must be accounted for [ 94 ]. Additionally, we recommend development of a separate default factor to account for exposure to multiple chemical and non-chemical stressors [ 95 , 96 ].…”
Section: Resultsmentioning
confidence: 99%
“…Federal programs such as Tox21, a collaboration between the National Institutes of Health (NIH), the Food and Drug Administration (FDA), the National Toxicology Program (NTP), and the EPA’s ToxCast program, use NAMs to generate chemical-specific in vitro concentration–response data in high-throughput screening (HTS) in vitro assays covering a wide range of human molecular and cellular targets . To date, these methods have been used for tier 1 screening of chemicals for estrogenic activity and for research and environmental screening purposes; however, they have not been used as the basis for setting hazard benchmarks. …”
Section: Introductionmentioning
confidence: 99%